The larvae of Phaenandrogomphus Lieftinck, 1964 in Thailand, including the description of P. tonkinicus (Fraser, 1926) with a larval diagnosis and new province records of P. asthenes Lieftinck, 1964 (Odonata: Gomphidae) - Novelo-Gutiérrez, Rodolfo; Sites, Robert W. (Zootaxa, 2019)
The larva of Phaenandrogomphus tonkinicus (Fraser, 1926) is described for the first time based on several F-0 larvae collected in Chiang Mai and Nan provinces of Thailand. The larva of P. tonkinicus differs from that of P. asthenes Lieftinck, 1964 by having the 3rd antennomere mesal margin strongly convex, 4th antennomere vestigial and dome-like, postclypeus thick and shelf-like, S8 lacking a posterolateral spine, and cerci usually shorter than the epiproct. New Thailand province records of P. asthenes also are provided.